Infiltrins as a novel regulatory principle of host-parasite interactions: new targets for vaccination? - Alouffi, Abdulaziz (2017)
Infiltrins, or pathogen-secreted host nucleus infiltrating proteins, are potential new targets for the development of more efficient vaccines against helminthic parasites. The archetypal infiltrin is IL-4 inducing principle from S. mansoni eggs (IPSE/alpha-1, also known as SmIPSE), a glycoprotein secreted by Schistosoma mansoni eggs, and characterised by the simultaneous presence of a classical secretory signal and a nuclear localisation signal. Within minutes following uptake by mammalian host cells, IP SE/alpha-1 translocates to their nucleus and binds to Deoxyribonucleic acid. This suggests that infiltrins, by acting as transcription factors, might play a central role in controlling the host-parasite relationship at the molecular level. Together with their secretory status, this role makes infiltrins interesting targets for vaccination. In this study, similar properties were demonstrated for nuclear localisation signal of ShIPSE03 (125-SKRRRKY-131) located between amino acid position 125 and 131, that plays a necessary and sufficient role in the process of transferring ShIPSE03 and heterologous GFP proteins into the nuclei of host cells. Similarly, a combination of online bioinformatics tools was used to predict the putative nuclear localisation signal motif of Smk5 (256-ELKRRVE-262) from S. mansoni eggs, and FhGST-si (202-LKKRAKT-208) and FhH2A (35-IHRHLKT-41) from Fasciola hepatica. To verify the predicted NLSs, putative infiltrins were used to generate a series of truncated constructs fused with Aequorea coerulescens green fluorescent protein-1 (AcGFP1), which were transfected into mammalian cells. Nuclear localisation of fluorescence confirmed the existence of a single, signal at the C-terminal in ShIPSE03, FhGST-si, and Smk5, and at the N-terminal in FhH2A. The predicted NLS motifs in ShIPSE03 (125-SKRRRKY-131), Smk5 (256-ELKRRVE-262), FhGST-si (202-LKKRAKT-208) and FhH2A (35-IHRHLKT-41) inserted into Tetra-enhanced green fluorescent protein (EGFP), but not corresponding alanine NLS mutants, redirected the encoded ~100 kDa protein entirely to the nucleus. Use of an IPSE-specific monoclonal antibody or an anti-His antibody showed that wild-type recombinant ShIPSE03, Smk5, FhGST-si and FhH2A added exogenously to HTB-9 or Huh7 cells, fully translocated to the nucleus, whereas the alanine NLS mutant remained in the cytoplasm. Overall, the existence of infiltrins in S. haematobium and F. hepatica suggests that infiltrins may represent a more general regulatory principle operating within parasitic trematodes. In terms of the function of IPSE/alpha-1, quantitative real-time polymerase chain reaction data indicated that an increase in Alanine-Transaminase (ALT) activity measured after 72 hours could be a result of increased gene expression after IPSE/alpha-1 nuclear translocation, rather than a true reflection of hepatotoxicity. According to Transepithelial Electrical Resistance (TEER) measurements in electrically tight Caco-2 cells grown in transwell inserts, wild-type IPSE/alpha-1 may play an important role in the down- regulation of intestinal epithelial cell tight junction integrity, might encourage apoptotic mediators and inflammatory responses in intestinal epithelial cells, and impair the intestinal tight junction barrier by causing it to dysfunction. In addition, wild-type IPSE/alpha-1 was able to activate humanised basophil reporter cell lines, such as the RS-ATL8 and NFAT DsRed cell lines.